2024
DOI: 10.3390/su16041377
|View full text |Cite
|
Sign up to set email alerts
|

Can Green Finance Mitigate China’s Carbon Emissions and Air Pollution? An Analysis of Spatial Spillover and Mediation Pathways

Huidong Liu,
Jing Yang,
Fang Zhao
et al.

Abstract: China faces a multi-objective environmental governance dilemma involving achieving fundamental ecological environment improvement, carbon peaking, and carbon neutrality. In this study, we constructed indicators of the level of green finance development through the entropy-weighted TOPSIS evaluation model, and adopted the two-way fixed-effect spatial Durbin model (SDM) and the multiple spatial mediation effect model to explore the impacts and paths of green finance as a policy tool to promote environmental sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Based on research by Li K. et al, it was found that during episodes of high temperatures accompanied by low winds, stagnant air at ground level contributes to increased ozone concentrations [71]. Additionally, according to a study by Jia, Li et al, among the six atmospheric pollutants they measured (SO 2 , NO 2 , PM10, PM2.5, CO, and O 3 ), sunshine duration had the most significant impact on ozone concentrations compared to the other five pollutants [72]. In this situation, ozone depends not only on the concentrations of the precursors but also on certain favorable weather conditions such as high temperature, low wind speed, and wind direction [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Based on research by Li K. et al, it was found that during episodes of high temperatures accompanied by low winds, stagnant air at ground level contributes to increased ozone concentrations [71]. Additionally, according to a study by Jia, Li et al, among the six atmospheric pollutants they measured (SO 2 , NO 2 , PM10, PM2.5, CO, and O 3 ), sunshine duration had the most significant impact on ozone concentrations compared to the other five pollutants [72]. In this situation, ozone depends not only on the concentrations of the precursors but also on certain favorable weather conditions such as high temperature, low wind speed, and wind direction [73,74].…”
Section: Discussionmentioning
confidence: 99%